On the measurement and prediction of rainfall noise. (1st January 2021) - Schmid, G.; Kingan, M.J.; Panton, L.; Willmott, G.R.; Yang, Y.; Decraene, C.; Reynders, E.; Hall, A.
Abstract: This paper concerns the measurement and prediction of rainfall noise with a particular focus on measurements made using the method described in the ISO rainfall noise standard. Rainfall noise is generated by rain impacting on a surface which excites the surface producing noise. Here, several different models for the force produced by a water droplet impacting on a flat inclined surface are presented. These models are designed for the nominal intense and heavy raindrops described in the ISO standard and are validated against experimental measurements. The best-performed models have been incorporated into theoretical methods for predicting the noise produced by rainfall on a flat inclined panel. These methods are used to produce noise level predictions for heavy rainfall on a standard reference test specimen which are compared with experimental measurements and show moderate agreement. These experiments were conducted using the test method described in the ISO standard. Several issues which we encountered implementing this test method are described and a number of suggestions are made to improve this method. Finally, the theoretical models are used to investigate the effect of different parameters on rainfall noise for the purpose of illustrating potential sources of error during testing using the ISO standard method.